Study of Hepatitis C virus infection at a tertiary hospital: Genotyping, risk factors and comorbidities - Abdul Rahman, Siti Nurul Fazlin; Hamzah, Hairul Aini; Hasmoni, Mohamed Hadzri; Mustafa Mahmoud, Mohammed Imad Al-Deen (International Islamic University Malaysia, 2017)
Introduction: Hepatitis C virus (HCV) genotyping is very important for the clinical management of HCV-infected patients. The aim of this study was to determine the genotypes of HCV-infected patients and to identify their risk factors and comorbidities. Materials and Methods: This was an observational, cross sectional study in which forty (40) HCV-infected patients attending Gastroenterology Clinic, Hospital Tengku Ampuan Afzan (HTAA) Kuantan Pahang were recruited for the study, from January to July 2014. Nucleotide sequence analysis of the 5’UTR and NS5B region were performed to identify the viral genotypes. Results: Of the 40 samples, 31 (77.5%) isolates were successfully classified into their genotypes and subtypes; 3a (57.5%), 1a (12.5%), 3b (2.5%) and 1b (2.5%). No genotype 2, 4, 5 and 6 were found in this study. However, there was one mixed-genotype (3a/1a) HCV infection. Risk factors and co-morbidities found in this study include IVDUs, haemodialysis, blood transfusion, surgery and co-infection with HIV. Conclusion: Genotype 3 followed by genotype 1 were the common HCV genotypes found in this study population. Furthermore, the highest risk factors and co-morbidities were IVDUs and co-infection with HIV.